2007
DOI: 10.1523/jneurosci.0322-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Sulfoxide Reductase A and a Dietary SupplementS-Methyl-L-Cysteine Prevent Parkinson's-Like Symptoms

Abstract: Parkinson's disease (PD), a common neurodegenerative disease, is caused by loss of dopaminergic neurons in the substantia nigra. Although the underlying cause of the neuronal loss is unknown, oxidative stress is thought to play a major role in the pathogenesis of PD. The amino acid methionine is readily oxidized to methionine sulfoxide, and its reduction is catalyzed by a family of enzymes called methionine sulfoxide reductases (MSRs). The reversible oxidation-reduction cycle of methionine involving MSRs has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
94
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 62 publications
(98 reference statements)
10
94
1
1
Order By: Relevance
“…Moreover, the methionine analog S-methyl-L-cysteine was recently found to delay the onset of motor deficits in α-synuclein transgenic flies, possibly by activating an MsrA-driven redox cycle [28]. These observations imply that the MsrA repair function is not the only activity involved in mitigating α-synuclein-induced cell death -rather, other functions such as MsrA-mediated ROS scavenging may also contribute to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the methionine analog S-methyl-L-cysteine was recently found to delay the onset of motor deficits in α-synuclein transgenic flies, possibly by activating an MsrA-driven redox cycle [28]. These observations imply that the MsrA repair function is not the only activity involved in mitigating α-synuclein-induced cell death -rather, other functions such as MsrA-mediated ROS scavenging may also contribute to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have reported that MsrA is neuroprotective in vitro [21,50] and in vivo [25], and data from one study indicate that MsrA levels are decreased in the brains of Alzheimer's disease patients compared to age-matched controls [51]. A very recent study revealed that MsrA alleviates motor dysfunction and neurodegeneration in transgenic flies over-expressing α-synuclein [28]. Our data are the first to show in a mammalian system that MsrA suppresses dopaminergic cell death and protein aggregation elicited by toxic phenomena involved in PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reverse reduction reaction is catalyzed by a family of enzymes called methionine sulfoxide reductases (MSRs). In a α-synuclein Drosophila model, overexpression of MSRA was found to prevent the decreased locomotor activity and shortened lifespan caused by elevated α-synuclein [53].…”
Section: α-Synucleinmentioning
confidence: 97%